Implemantation of industrialized building system / Ahmad Hafiz Hizri Zulkefli - Zulkefli, Ahmad Hafiz Hizri (Universiti Teknologi MARA, Perak, 2018)
Industrialized Building System (IBS) is a new construction technique or methods that intended to replace the aging conventional building system. This report particularly will discuss the Implementation of IBS in Malaysia specifically in project Hospital Bachok which currently under construction with 50% completion. The report will comprise the type of IBS being uses in Malaysia together with the advantages of adapting this new technique in modem construction. All the data collected for this report has been done by on-site inspection during the internship session. A few individuals also have been interviewed together with doing mass media and document analysing.